2007
DOI: 10.1128/aem.00517-07
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sublethal Injury and Inactivation of Yeast Cells by the Combination of Sorbic Acid and Pulsed Electric Fields

Abstract: The objective of this study was to investigate the occurrence of sublethal injury after the pulsed-electric-field (PEF) treatment of two yeasts, Dekkera bruxellensis and Saccharomyces cerevisiae, as well as the relation of sublethal injury to the inactivating effect of the combination of PEF and sorbic acid. PEF caused sublethal injury in both yeasts: more than 90% of surviving D. bruxellensis cells and 99% of surviving S. cerevisiae cells were sublethally injured after 50 pulses at 12 kV/cm in buffer at pHs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
8
36
0
Order By: Relevance
“…The extent of sublethal injury after HHP treatment was also greater at pH 4.0 than at pH 7.0 in E. coli and L. monocytogenes, whereas in S. cerevisiae, injury did not depend on the treatment medium pH. As with pressure, the occurrence of sublethal injury in yeast after PEF has been shown to be independent of the treatment medium pH (54). The similarity in the effect of pH on inactivation and injury by HHP and PEF may perhaps be related to the fact that the cytoplasmic membrane is a major target for damage in both processes (40).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The extent of sublethal injury after HHP treatment was also greater at pH 4.0 than at pH 7.0 in E. coli and L. monocytogenes, whereas in S. cerevisiae, injury did not depend on the treatment medium pH. As with pressure, the occurrence of sublethal injury in yeast after PEF has been shown to be independent of the treatment medium pH (54). The similarity in the effect of pH on inactivation and injury by HHP and PEF may perhaps be related to the fact that the cytoplasmic membrane is a major target for damage in both processes (40).…”
Section: Discussionmentioning
confidence: 84%
“…Both bacterial species were more sensitive to pressure at acidic pHs, as expected, but there was no difference in the resistance of S. cerevisiae when the yeast was pressurized at pH 7.0 or pH 4.0. This might be regarded as unexpected, though survival of S. cerevisiae during pulsed electric field (PEF) treatment was similarly unaffected by pH (54). The extent of sublethal injury after HHP treatment was also greater at pH 4.0 than at pH 7.0 in E. coli and L. monocytogenes, whereas in S. cerevisiae, injury did not depend on the treatment medium pH.…”
Section: Discussionmentioning
confidence: 86%
“…The raw juice was inoculated with a mix of both strains (3 log 10 CFU/ mL). The evaluation of yeast sublethal injury was conducted according to the plate methods proposed by Somolinos et al (2007). In order to assess the cell injury, OGYE medium was added with 5% w/v NaCl and 12% w/v NaCl, respectively.…”
Section: Us Treatment and Calorimetrymentioning
confidence: 99%
“…However, only C. parapsilosis showed a significant level of sublethally-injured cells in sonicated juices (Mann-Whitney test: p = 0.01; Figure S3). In general, sublethally-injured cells became sensitive to many selective compounds due to the damage of their membranes and modification of their permeability (Jasson et al, 2007;Somolinos et al, 2007). Furthermore, other studies demonstrated the presence of sublethally-injured yeasts after non-thermal processing, such as pulsed electric fields (Somolinos et al, 2007).…”
Section: Sublethal Injury Evaluation In R Glutinis and C Parapsilosismentioning
confidence: 99%
See 1 more Smart Citation